Metal Accumulations in Two Extreme-Environment Amphipods, Hadal Eurythenes gryllus and Antarctic Pseudorchomene plebs - Shaojun Huang; Lingyue Zhu; Shouwen Jiang; Wanying Zhai; Binbin Pan; Zhichao Wu; Qianghua Xu (Journal of Marine Science and Engineering, 2023)
The hadal zone and Antarctic Ocean are two of the least-explored habitats. Knowledge about human impacts on these two extreme environments is limited. Here, we analyzed the metal accumulations of two amphipod species, Eurythenes gryllus, from the Mariana Trench (6040 m, 11.36° N, 142.41° E) in the West Pacific Ocean, and Pseudorchomene plebs, from the Ross Sea (600 m, 77.12° S, 167,67° E) in the Antarctic. Bioaccumulation of thirteen elements (Na, Mg, K, Ca, Cu, Fe, Al, Cr, Mn, Zn, As, Se, and Cd) in three tissues (exoskeleton, leg muscle, and gut) of the two amphipods was investigated using inductively coupled plasma mass spectrometry (ICP-MS). Comparing the trace element concentrations between the different amphipoda species, we found higher element concentrations in the Antarctic amphipod, and an oligotrophication of the Mariana Trench. The concentrations of Cu, Zn, As, and Se in the three tissues all had a significant difference in abundance, and the Cd in the gut of P. plebs was comparably higher than that in E. gryllus, consistent with special environment adaptation. Compared with non-abyssal and shallow water decapoda and amphipoda species, hadal amphipods possessed comparably higher concentrations of Cd and Cr elements and displayed a very high environmental specificity for amphipods’ metal-element bioaccumulation strategy. This study reveals the amphipods of remote and uncontaminated areas as potential indicator species for metal-element bioaccumulation to measure anthropogenic impacts.